Modelling the Deceleration Rate in the Train Braking Profile - Abal Abas , Zuraida; Shutler, Maurice (2007)
This paper deals with the analysis of deceleration rate in the train braking profile for one of major transportations company in the Europe The aim is to establish the relation between the declaration rate and the factor preferred by the client. Of all the factors, the most preferred factor was an average gradient experienced by each train. The method used in this paper is hard technique of Operational Research. Mathematical calculation is used to generate the average gradient experienced by each train which will be used to match which with the deceleration rate to established the relation between these two variables using regression analysis. As a conclusion, there was a relation between deceleration rate and average gradient experienced by the train and it was noticeable that driver's actual braking performance of applying deceleration rate was affected by the varying gradient more than constant gradient. As an additional work, the relation between braking distance and deceleration rate is also established. The model can be used as an initial study to determine the distance when the driver should start to brake optimally in further study.